Psychological capital mediates the relationship between medication adherence and cancer-related fatigue in breast cancer patients undergoing long-term treatment - Yan, Chunli; Chu, Yane (Frontiers in Psychiatry, 2025)
BackgroundBreast cancer is one of the most prevalent malignant tumors among women worldwide. Although long-term pharmacological treatment has substantially improved survival rates, it is often accompanied by psychological burdens, including cancer-related fatigue (CRF) and diminished adherence to therapy. CRF is a pervasive and debilitating symptom that adversely affects physical functioning and emotional well-being. Psychological capital (PsyCap), a construct encompassing self-efficacy, hope, optimism, and resilience, has been shown to enhance treatment engagement and promote mental health. However, its role as a potential psychological mediator between medication adherence and CRF is yet to be thoroughly investigated.ObjectiveTo investigate the mediating role of PsyCap in the relationship between medication adherence and CRF in patients with breast cancer undergoing long-term treatment.MethodsA total of 100 breast cancer patients admitted between June 2022 and June 2024 were recruited using convenience sampling. Data from 90 valid responses were analyzed. Participants completed the PsyCap Questionnaire (PCQ-24), Self-Reported Medication Adherence Rating Scale (SR-MARS), and CRF Scale (CFS). Pearson’s correlation analysis was used to assess associations among variables. A mediation analysis was conducted using the bootstrap method with 5,000 resamples.ResultsThe mean scores for PsyCap, medication adherence, and CRF were 86.65 ± 8.37, 5.36 ± 1.12, and 36.77 ± 5.98, respectively. PsyCap was positively correlated with medication adherence (r = 0.994, p < 0.05) and negatively correlated with CRF (r = –0.992, p < 0.05). Medication adherence was also negatively correlated with CRF (r = –0.994, p < 0.05). Mediation analysis confirmed that PsyCap significantly mediated the relationship between medication adherence and CRF (indirect effect = 0.357, 95% CI did not include zero), accounting for 55.68% of the total effect.ConclusionPsyCap partially mediated the association between medication adherence and CRF. Interventions aimed at enhancing PsyCap may improve adherence and reduce CRF in breast cancer patients receiving long-term pharmacotherapy.